SDDGR: Stable Diffusion-Based Deep Generative Replay for Class Incremental Object Detection - Kim, Junsu; Cho, Hoseong; Kim, Jihyeon; Tiruneh, Yihalem Yimolal; Baek, Seungryul (Proceedings (IEEE Computer Society Conference on Computer Vision and Pattern Recognition. Online), 2024)
In the field of class incremental leaming (CIL), generative replay has become increasingly prominent as a method to mitigate the catastrophic forgetting, alongside the continuous improvements in generative models. However, its application in class incremental object detection (CIOD) has been significantly limited, primarily due to the complexities of scenes involving multiple labels. In this paper, we propose a novel approach called stable diffusion deep generative replay (SDDGR) for CIOD. Our method utilizes a diffusion-based generative model with pre-trained text-to-image diffusion networks to generate realistic and diverse synthetic images. SDDGR incorporates an iterative refinement strategy to produce high-quality images encompassing old classes. Additionally, we adopt an L2 knowledge distillation technique to improve the retention of prior knowledge in synthetic images. Furthermore, our approach includes pseudo-labeling for old objects within new task images, preventing misclassification as background elements. Extensive experiments on the COCO 2017 dataset demonstrate that SD-DGR significantly outperforms existing algorithms, achieving a new state-of-the-art in various CIOD scenarios.